The Evaluation of the Addition of Commercial Yeast with β -Glucan Content in Feed on the Immunity of Snakehead Fish Channa striata Infected by Aeromonas hydrophila Bacteria - Tiara Puspa Anjani; Dinamella Wahjuningrum; Sri Nuryati; Ikhsan Khasani (Journal of Aquaculture and Fish Health, 2021)
Snakehead fish Channa striata is a high commercial freshwater fish commodity. It has the potential as a pharmaceutical ingredient. Intensive snakehead fish cultivation starts to experience a problem, namely Motile Aeromonas Septicemia (MAS) caused by Aeromonas hydrophila. The purpose of this study is to evaluate the effect of the addition of commercial yeast in feed to improve snakehead fish immunity. This study was designed with a completely randomized design (CRD) with 5 treatments with 3 replications (reared in the net) and 6 treatments with 3 replications (reared in the aquarium). The treatments were K (feed without yeast), F5 (feed with the addition of 5 g/kg of cake yeast), R3 (feed with the addition of  3 g/kg of tempeh yeast, R5(feed with the addition of 5 g/kgof tempeh yeast), and R7 (feed with the addition of 7 g/kg of tempeh yeast). The results show that the survival rate after 30 days is 88.89- 92.22%. The best treatment after A. hydrophila infection was found in fish fed with 3 g/kg oftempehyeast with a survival rate of 56.67%, total erythrocytes of 4.07x 106 mm-3 cells, hemoglobin of 7.40 g% of total leukocytes 4.97x 104 mm-3 cells and phagocytic activity of 33.67. In conclusion, the addition of tempeh yeast at a dose of 3 g/kg could be used as an alternative to prevent the effect of A. hydrophila pathogen infection in snakehead fish.